Activity in dlPFC and its effective connectivity to vmPFC are associated with temporal discounting - Hare, Todd A.; Hakimi, Shabnam; Rangel, Antonio (Frontiers in Neuroscience, 2014)
There is widespread interest in identifying computational and neurobiological mechanisms that influence the ability to choose long-term benefits over more proximal and readily available rewards in domains such as dietary and economic choice. We present the results of a human fMRI study that examines how neural activity relates to observed individual differences in the discounting of future rewards during an intertemporal monetary choice task. We found that a region of left dlPFC BA-46 was more active in trials where subjects chose delayed rewards, after controlling for the subjective value of those rewards. We also found that the connectivity from dlPFC BA-46 to a region of vmPFC widely associated with the computational of stimulus values, increased at the time of choice, and especially during trials in which subjects chose delayed rewards. Finally, we found that estimates of effective connectivity between these two regions played a critical role in predicting out-of-sample, between-subject differences in discount rates. Together with previous findings in dietary choice, these results suggest that a common set of computational and neurobiological mechanisms facilitate choices in favor of long- term reward in both settings.